Police Ethics - Richard Lewis (The Journal of Intelligence, Conflict and Warfare, 2022)
On November 25, 2021, Chief Cst. Richard Lewis from Cleveland Police (United Kingdom) presented Police Ethics at the 2021 CASIS West Coast Security Conference. The presentation was followed by a question and answer period. The key points discussed were police ethics in the United Kingdom (UK), the role of the National Police Ethics Committee, and public involvement to maintain a trusting relationship between the public and law enforcement.